2021
DOI: 10.3390/v13020279
|View full text |Cite
|
Sign up to set email alerts
|

TRIMming Type I Interferon-Mediated Innate Immune Response in Antiviral and Antitumor Defense

Abstract: The tripartite motif (TRIM) family comprises at least 80 members in humans, with most having ubiquitin or SUMO E3 ligase activity conferred by their N-terminal RING domain. TRIMs regulate a wide range of processes in ubiquitination- or sumoylation-dependent manners in most cases, and fewer as adaptors. Their roles in the regulation of viral infections, autophagy, cell cycle progression, DNA damage and other stress responses, and carcinogenesis are being increasingly appreciated, and their E3 ligase activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 241 publications
1
28
0
Order By: Relevance
“…TRIM21 is a member of the TRIM superfamily, which has been reported to be involved in diverse biological processes and implicated in various diseases (Wang L and Ning S, 2021). Our previous study showed an important role of TRIM21 in the virus-triggered RLR signaling pathway (Lee AYS et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM21 is a member of the TRIM superfamily, which has been reported to be involved in diverse biological processes and implicated in various diseases (Wang L and Ning S, 2021). Our previous study showed an important role of TRIM21 in the virus-triggered RLR signaling pathway (Lee AYS et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…TRIM21 is one of the members of the tripartite motif (TRIM) superfamily, which plays an important role in diverse biological and pathophysiological processes, including systemic autoimmune diseases, such as systemic lupus erythematosus (SLE), antiviral innate immunity and cancer proliferation (Wang L and Ning S, 2021, Lee AYS et al, 2021, Xue B et al, 2018. Our previous study showed that TRIM21 interacts with MAVS and catalyzes the K27-linked ubiquitination of MAVS to restrict viral infection by promoting the innate immune response to viral infection (Xue B et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, several human pathogenic viruses can successfully develop immune evasion by various molecular mechanisms, including the induced expression of immune checkpoints, like PD-L1 and HLA-G, in the virus-infected host cells (1,(71)(72)(73). In this review, we will summarize known examples of human viruses able to induce immunological tolerance towards host immune effector cells by HLA-G induction.…”
Section: Regulation Of Hla-g Expression and Viral Infectionsmentioning
confidence: 99%
“…Viruses promote viral replication and pathogenesis by interfering with host ubiquitin-dependent signaling pathways or by hijacking the cellular ubiquitination machinery [9] , [10] , [11] . There are well-established examples where the viral proteins bind to RING E3s.…”
Section: Introductionmentioning
confidence: 99%